URGENSI PEMBELAJARAN SEX EDUCATION BAGI SISWA UNTUK MENCEGAH PENYIMPANGAN SEKSUAL DI SDN 2 SIMBANG - Dwi Umul Hasanah; Titis Anjarwati; Hidayatu Munawaroh (INSTRUKTUR, 2023)
This study aims to explain and increase students' understanding of the influence of sexual education at SD N 2 Simbang. The results of this study are used as a guide for students in understanding their puberty. This research is included in the descriptive quantitative research. The research was conducted at SD N 2 Simbang with the research subjects being grade VI students at SD N 2 Simbang and teachers at SD N 2 Simbang. The sampling technique used saturated sampling and purposive sampling, so that all class VI students at SD N 2 Simbang and their homeroom teachers played a role in collecting research data. The instruments used include interview guides, observation sheets, and questionnaires. Dealing with cases of sexual harassment, including poking peers, saying words that lead to things that children don't usually say, either directly or via the media. The results of the study show that the opinion of some teachers is that for them sexual learning is not needed because when they face puberty they will know it by themselves or naturally. However, from the cases that occurred, it is evident that sex education education is very much needed by students from teachers in the school environment, because teachers are substitutes for parents at home. Therefore, sex education education should have been implemented in schools as an introduction for students to adapt when they enter puberty